UPAYA PASTORAL KONSELING BAGI PEMUDA YANG MENGALAMI TRUST ISSUE AKIBAT KONFLIK SAAT BERPACARAN - Lanongbuka, Amartya Lovelin; Luma, Subaedah (PT. Giat Konseling Nusantara, 2024)
Trust issue is a situation where a person becomes a person who does not easily trust other people. Trust issues can cause things that can be detrimental to the person who experiences them in the future, such as causing disappointment and missing important moments in life. Trust issues mostly arise among young people who are already dating and have a negative impact on the survival of these young people both psychologically and socially. For this reason, the aim of this research is to describe the impact of trust issues experienced by young people and pastoral counseling efforts regarding trust issues among young people. The method used in this research is a descriptive research method, with data collection through observation and interviews with several young people in Bira Village. The results of this research show that the trust issues experienced by the subjects are fear of building new relationships, always having negative prejudices towards partners and also people around them, both friends and family, and some are afraid to get married. For this reason, pastoral counseling is a service effort that can help subjects experience positive changes and get out of their problems, and experience holistic healing.